Mixed cryoglobulinaemic vasculitis with pulmonary infiltrates and cavitation. Issue 9 (7th September 2022) - Masnammany, Adrian Mark; Wong, Peter Kee Kee; Ng, Beverly Cheok Kuan; Manolios, Nicholas
Abstract : Cryoglobulinaemic vasculitis is an immune complex-mediated vasculitis with a myriad of clinical manifestations. We report a rare case of a patient in her 60s with rheumatoid arthritis who presented with fever of unknown origin, cutaneous leucocytoclastic vasculitis and progressive pulmonary infiltrates with cavitation. Extensive investigation for an infectious aetiology was unrevealing. Blood investigations revealed high-titre rheumatoid factor, hypocomplementaemia, raised inflammatory markers and the presence of type 2 cryoglobulins. A diagnosis of cryoglobulinaemic vasculitis with pulmonary involvement was made, and the patient was treated with high-dose prednisolone and rituximab, which resulted in complete resolution of lung changes and marked clinical improvement. This case highlights the rarity of lung involvement, including cavitation in cryoglobulinaemic vasculitis.